Метод обработки реограммы легкого с использованием вейвлет-технологии - Величко, О. Н.; Карпенко, С. А.; Пащенко, А. А.; Попов, А. В. (НТУ "ХПИ", 2008)
Проанализированы достоинства и недостатки метода обработки реограммы сегмента легкого на вдохе и выдохе. Показаны преимущества вейвлетного анализа для исследования тонкой структуры реограмм и предложен метод интерпретации результатов сегментарной реографии легких на базе технологии дискретного вейвлетного анализа.

Advantages and disadvantages of the method of delivery the rheogram of lungs for different respiratory phases were analyzed. Wavelet analysis advantages for research of rheogram fine structure for inspiration and expiration were revealed. The interpretation method of lung segment rheography results, based on digital wavelet analysis was offered.
Method of delivery the rheogram of lungs, based on wavelet analysis
Keywords: рентгенографические методы; вейвлетный анализ; сегментарная реография легких; легочные патологии; реографические сигналы; rheogama; wavelet analysis; box-type rheograph lungs